2021
DOI: 10.3390/fluids6060223
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Thermal Behavior of a New Structure of Protected Agriculture Established in a Region of Tropical Climate Conditions

Abstract: Determining airflow patterns and their effect on the distribution of microclimate variables such as temperature is one of the most important activities in naturally ventilated protected agricultural structures. In tropical countries, this information is used by farmers and decision makers when defining climate management strategies and for crop-specific cultural work. The objective of this research was to implement a validated Computational Fluid Dynamics (CFD) model in 3D to determine the aerodynamic and ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 65 publications
(81 reference statements)
1
5
0
1
Order By: Relevance
“…It is worth mentioning that the qualitative characteristics of the air flow patterns discussed in this section are influenced by the loss of impulse presented on the air flow due to the presence of the anti-insect screen. Likewise, the flow pattern inside the IP-SH is driven by the wind and thermal components of natural ventilation, this type of results has already been discussed and verified in similar works such as those developed by Flores-Velá zquez & Montero [10] and Villagrá n & Rodriguez [31]. Results that have been experimentally validated as reported by Teitel et al [8,49].…”
Section: Air Flow Patternssupporting
confidence: 77%
See 1 more Smart Citation
“…It is worth mentioning that the qualitative characteristics of the air flow patterns discussed in this section are influenced by the loss of impulse presented on the air flow due to the presence of the anti-insect screen. Likewise, the flow pattern inside the IP-SH is driven by the wind and thermal components of natural ventilation, this type of results has already been discussed and verified in similar works such as those developed by Flores-Velá zquez & Montero [10] and Villagrá n & Rodriguez [31]. Results that have been experimentally validated as reported by Teitel et al [8,49].…”
Section: Air Flow Patternssupporting
confidence: 77%
“…This is a semi-empirical model based on the transport equations that solve the kinetic turbulent energy ε and the dissipation of this energy per unit volume ε. The kε has been the most applied and widely validated model in greenhouse and screenhouse airflow studies showing to be computationally efficient while providing realistic solutions [14,31]. Boussinesq's model was considered in order to simulate variations in air density inside the screenhouse generated by temperature changes.…”
Section: Cfd Modelmentioning
confidence: 99%
“…This work identified that a greenhouse-shade-screen hybrid structure in semi-arid climatic conditions showed a lower thermal gradient compared to a greenhouse with a plastic cover, enabling vegetable production. It should also be mentioned that when solar radiation data for the study region are not available, these values can be obtained from the solar calculator of the Ansys Fluent software, and these values from the solar calculator can be coupled to any of the radiation models available in the software [4]. Finally, these coupled simulations in recent years have allowed the evaluation of different covering materials, which helps producers or decision makers to select the covering material with the best microclimate conditions, better PAR radiation utilization, and higher thermal efficiency in protected agriculture structures [135].…”
Section: Radiation Model Number Of Documents Referencementioning
confidence: 99%
“…This, together with the high vulnerability of agriculture due to accelerated climate change, has become a serious threat to the food security of nations, generating new challenges to agricultural productivity [3]. Therefore, there is an explicit need to increase food production by approximately 70% in the coming years, and it is also necessary to develop production intensification strategies to provide technical solutions [4]. The increase in food production must also be carried out with less natural resources, such as water and soil, which is why agriculture under cover or in greenhouses has been proposed as one of the main production alternatives [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation